IMPLEMENTASI USER ACCEPTANCE TESTING (UAT) PADA RANCANG BANGUN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) - Dwi Diana Sari; Mariana Purba; Nia Umilizah (Institute for Research and Community Service, 2024)
Purpose: The purpose of this test is to ensure that the main features of the system meet the needs and specifications that have been set. From a total of 9 test scenarios, 7 scenarios were successfully passed, while 2 scenarios failed, namely in the Document Upload feature (KK, Ijazah) and Print Proof of Registration. Methods/Study design/approach: The results of User Acceptance Testing (UAT) - Alpha Testing for the New Student Admission Information System (PPDB) conducted by the internal QA team at the research object, namely SMK Negeri 3 Kayu Agung. Result/Findings: This failure indicates the need for further development, as both features are crucial elements in the registration process. Based on the test results, future research is recommended to address these issues immediately so that the system can operate properly. The final decision concludes that the system is not ready for Beta Testing until all issues are resolved. Novelty/Originality/Value: This research with UAT evaluation aims to provide insights for future research and development regarding the readiness status of the system as well as the corrective measures needed to improve the user experience.